2022
DOI: 10.1111/1467-8268.12657
|View full text |Cite
|
Sign up to set email alerts
|

Does ICT diffusion contribute to women's political empowerment in Africa?

Abstract: In this article we investigate the effects of information and communication technologies (ICT) on women's political empowerment (WPE) from a sample of 51 African countries. We specify and estimate a panel data model by using the ordinary least squares (OLS) and two‐stage least squares (2SLS) over the period 1996–2017. The results show that ICT diffusion, measured by mobile phone and internet penetration, significantly increases WPE. This suggests an improvement of the institutional framework governing the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The vector of control variables X is made up of: (i) GDP per capita growth (annual %), the increase of which enhances the resilience of economies to exogenous shocks through a better distribution of goods (Kalantaryan et al, 2022); (ii) human capital, approximated by the number of students enrolled in secondary school, accounting for the ability to acquire and internalize new technologies (Mainuddin et al, 2015); (iii) access to electricity, referring to the percentage of the total population with access to electricity (Ongo et al, 2022a); (iv) financial development, measured by the volume of financial resources provided to the private sector by financial institutions. It increases the availability of credit, reduces information asymmetry, and promotes remittances (Asongu et al, 2016); (v) Internet penetration, measured by the population's Internet subscription rate (Adalbert Abraham Ghislain, 2022; Ongo et al, 2022b). It facilitates domestic and international financial transactions (Ongo & Song, 2022).…”
Section: Methodological Strategymentioning
confidence: 99%
“…The vector of control variables X is made up of: (i) GDP per capita growth (annual %), the increase of which enhances the resilience of economies to exogenous shocks through a better distribution of goods (Kalantaryan et al, 2022); (ii) human capital, approximated by the number of students enrolled in secondary school, accounting for the ability to acquire and internalize new technologies (Mainuddin et al, 2015); (iii) access to electricity, referring to the percentage of the total population with access to electricity (Ongo et al, 2022a); (iv) financial development, measured by the volume of financial resources provided to the private sector by financial institutions. It increases the availability of credit, reduces information asymmetry, and promotes remittances (Asongu et al, 2016); (v) Internet penetration, measured by the population's Internet subscription rate (Adalbert Abraham Ghislain, 2022; Ongo et al, 2022b). It facilitates domestic and international financial transactions (Ongo & Song, 2022).…”
Section: Methodological Strategymentioning
confidence: 99%
“…The key elements in the agenda for sustainable development include women's empowerment and gender equality which warrant the broadening of the range of opportunities to bridge the gender gap. The sustainable empowerment of women engulfs reducing inequality, and educational and financial inclusion as part of boosting the socioeconomic development processes (Tchamyou et al, 2019;Nkoa et al, 2022). Women work more unpaid hours in many nations, and they have fewer opportunities to use education and skills to escape poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the benefits of ICTs go beyond the economic aspects of growth, financial development or poverty. Indeed, Ongo Nkoa et al (2022) have shown that the high diffusion of ICTs in Africa over the past decades significantly improves women's political empowerment.…”
Section: Selective Review Of the Literaturementioning
confidence: 99%